REVEALS land-cover reconstructions for Europe during the Late Pleistocene (75-15 ka BP) - Oliver A Kern; Andreas Maier; Nikki Vercauteren (PANGAEA, 2025)
We present the first pollen-based REVEALS land-cover reconstructions of Europe during the late Last Glacial period from Europe. The results are based on fossil pollen data from 61 sites in Europe and bordering regions, using 38 plant taxa in total. The reconstruction uses the "Regional Estimates of VEgetation Abundance from Large Sites"(REVEALS) model that factors in the relative pollen productivity (RPPs) and fall speed of pollen (FSP) (Sugita, 2007). All REVEALS estimates and their Standard Erorrs are given in proportions for each site in 1kyr time steps from 75 to 15 ka BP. Moreover, we provide the RPP and FSP table, which was adapted from Githumbi et al. (2022) and Serge et al. (2023). We also include REVEALS land-cover reconstructions of the same dataset, using the RPP compilation of Wieczorek & Herzschuh (2020) as well as optimized RPP data after Schild et al. (2024) to highlight the impact of different RPP data on REVEALS land-cover reconstructions.